(3eYLe GdeUWdMGJ GdabgjI hGdbGfhfjI (B/s - (3LQLS, LQLSs; (3GdfGTa(B: (3GfWhGfs (Beirut : Sharikah al-'Alamiyah lil-Kitab, 1996)
Arabic-Arabic dictionary of legal terms
Keywords: Islamic law -- Dictionaries -- Arabic; Law -- Dictionaries -- Arabic